Shiga toxin-producing Escherichia coli: detection and isolation from swine feces and wheat grains by PCR and culture methods - Remfry, Sarah Elizabeth (Kansas State University, 2020)
Shiga toxin-producing Escherichia coli (STEC) are major foodborne pathogens that cause mild to hemorrhagic colitis, which could lead to a serious complication of renal failure, called hemolytic uremic syndrome, particularly in children. Seven serogroups of STEC, O26, O45, O103, O111, O121, O145, and O157, often called top-7, account for most of the STEC-associated illness in humans in the United States. Two Shiga toxins, Shiga toxin 1 and 2, encoded by stx1 and stx2, respectively, and intimin, a protein that mediates attachment of STEC onto enterocytes, encoded by eae gene, are major virulence factors involved in STEC infections. Cattle are a major reservoir of the ‘top-7’ serogroups, in which STEC colonize the hindgut and are shed in the feces. The feces serve as a major source of food, feed and water contaminations. In addition to cattle, other domestic animals and even wild animals harbor STEC and shed them in the feces. Sources of STEC foodborne illness outbreaks have been traced to food of animal and plant origin. Two studies were conducted to detect and isolate STEC, based on culture- and PCR methods, from swine feces and wheat grains. Swine fecal samples (n=598), collected from ten swine farms with finisher pigs, located in eight states, were enriched with EC broth. The enriched samples were subjected to a three-plex quantitative PCR (qPCR) assay targeting three virulence genes, stx1, stx2, and eae. Samples positive for either of the two Shiga toxin genes were then tested by a multiplex PCR assay targeting top-7 serogroups (O26, O45, O103, O111, O121, O145, and O157) and the O104 serogroup. Also, stx-positive samples were subjected to an eight-plex PCR assay, designed and validated to detect 8 serogroups (O8, O20/O137, O59, O86, O91, O100, O120, and O174) considered to be the top-8 prevalent STEC in swine feces. Samples positive for the top-7 plus O104 serogroups were subjected to a serogroup-specific IMS culture method and plating on selective media for detection and isolation of top-7 serogroups of STEC. Samples positive for stx1 or stx2 gene and negative for the top-7 serogroups were directly plated onto MacConkey and Eosin-Metheylene Blue agar. Putative colonies, up to ten per sample and medium, were picked, pooled and tested for stx genes. If pooled colonies were positive for stx1 or stx2 gene, then each colony in the pool was tested individually to identify stx1 and/or stx2-carrying E. coli. Of the 598 fecal samples tested by qPCR for the three major virulence genes, 155 (25.9%), 389 (65.1%), and 398 (66.6%) samples were positive for stx1, stx2, and eae genes, respectively. Based on the mPCR assay for the top-7 plus O104 serogroups, the three predominant serogroups detected were O26 (10.7%; 64/598), O121 (17.6%; 105/598), and O157 (11.5%; 69/598). The 8-plex PCR assay designed to detect the top-8 serogroups of swine STEC indicated the prevalence of 88.6% of O8 (530/598), 35.5% of O86 (212/598), 24.1% of O174 (144/598), 20.2% of O100 (121/598), 15.6% of O91, 4.3% of O59 (26/598), 4.2% of O120 (25/598), and 3.2% of O20/O137 (19/598). The culture method identified STEC O121 as the dominant top-7 STEC serogroup (3.8%; 23/598). None of the O157 isolates (3.5%; 21/598) carried the stx gene. Isolates that were non top-7 (or O104) were tested by 12 different PCR assays that can detect 130 serogroups to identify the serogroups of STEC. The most prevalent non top-7 STEC serogroups isolated were STEC O8 and STEC O86. In conclusion, our study indicated that the major top-7 STEC was O121, and among the non-top-7 STEC, serogroups of O8 and O86 were the dominant. Interestingly, the O157 serogroup implicated in outbreaks traced to pork products, was shed in the feces, but none of the isolates carried the stx gene. Data on the prevalence and virulence potential of STEC from swine will be useful information to have to evaluate management strategies and mitigate the effects on food borne illnesses in the United States. Wheat grain samples (n=626), collected from different regions of the country and transported to the laboratory, were enriched using two different media, modified Buffered Peptone Water with pyruvate (mBPWp) and Escherichia coli (EC) broth and subjected to a mPCR assay to detect the top-7 serogroups (O26, O45, O103, O111, O121, O145, and O157) and three major virulence genes (stx1, stx2, and eae). Samples positive by PCR for any of the top-7 serogroups and or stx genes were then cultured using serogroup-specific immunomagnetic separation (IMS) and plating on selective media for detection and isolation of top-7 STEC. Based on the mPCR assay, the prevalence of the top-7 serogroups in wheat grain samples, enriched by mBPWp, were 0.2% of O26 (1/626), 0.6% of O45 (4/626), 0.2% of O103 (1/626), and 0.6% of O157 (4/626), and the prevalence of virulence genes were 0.2% of stx1 (1/626), 0.2% of stx2 (1/626), and 0.8% of eae (5/626). The prevalence of top-7 serogroups, enriched in EC broth, were 0.2% of O26 (1/626), 1.9% of O45 (12/626), 0.5% of O103 (3/626), and 1.0% of O157 (6/626), and that of virulence genes were stx1 (0.3%; 2/626), stx2 (1.3%; 8/626), and eae (1.1%; 7/626). The number of wheat grain samples positive for STEC serogroups and or virulence genes, by PCR method (36/626; 5.8%), was higher in samples enriched by EC broth than mBPWp broth (15/626; 2.4%). Based on culture methods, the top-7 serogroups prevalent in wheat grain samples, enriched in mBPWp, were 0.2% of O26 (1/626), 0.5% of O45 (3/626), 0.2% of O103 (1/626), and 0.6% of O157 (4/626), and none of the isolates was positive for any of the three virulence genes. In wheat grain samples enriched in EC broth, the prevalence of the top-7 serogroups were 0.2% of O26 (1/626), 0.8% of O45 (5/626), 0.3% of O103 (2/626), and 0.8% of O157 (5/626), with no detection of virulence genes. The number of wheat grain samples positive for STEC serogroups and or virulence genes, by culture method, was higher in samples enriched by EC broth than mBPWp broth (5/36 and 0/15, respectively). None of the isolates of the top-7 serogroups by either enrichment method was positive for the Shiga toxin genes. A total five isolates that carried the Shiga toxin 2 gene were isolated from wheat grains enriched in EC broth. The five isolates were confirmed as serogroups O8 (0.64%; 4/626) and O130 (0.16%; 1/626) by PCR. Our study shows that wheat grains were contaminated with the top-7 serogroups of E. coli, but none of the isolates carried the Shiga toxin genes. The two stx2-positive serogroups that were isolated, O8 and O130, are not major STEC pathogens and have only been implicated in sporadic diarrheal cases in animals and humans.
Keywords: Shiga toxin; Top-7; Wheat; Swine; Foodborne; Finisher pigs